2018
DOI: 10.1002/gps.5013
|View full text |Cite
|
Sign up to set email alerts
|

Clock drawing and neuroanatomical correlates: A systematic review

Abstract: Objective The popular clock drawing test (CDT) is easy to administer, acceptable to patients, and has excellent psychometric properties. Although it has been used primarily as a cognitive screening test, many studies have attempted to establish the CDT's ability to localize specific brain lesions or pathology. This systematic review aimed to summarize the evidence on the neuroanatomical correlates of the CDT. Methods Using PRISMA guidelines, the authors systematically reviewed the evidence on neuroanatomical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…Group 3 (impaired in the pre‐drawn CDT) was associated with GM volume reduction in the right middle and inferior temporal gyri. These results are consistent with a previous review that suggested the involvement of various brain regions in CDT, among which the bilateral temporal lobes have been implicated in many papers 18 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Group 3 (impaired in the pre‐drawn CDT) was associated with GM volume reduction in the right middle and inferior temporal gyri. These results are consistent with a previous review that suggested the involvement of various brain regions in CDT, among which the bilateral temporal lobes have been implicated in many papers 18 …”
Section: Discussionsupporting
confidence: 93%
“…Group 3 was suggested to be related to GM volume reduction in the right temporal gyrus. A previous systematic review reported the involvement of various brain regions in the performance of pre‐drawn CDT 18 . Some papers have highlighted the neurological correlation between CDT failure and the right inferior temporal gyrus, right superior temporal gyrus, and fusiform gyrus 13,15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this type of association was expected because according to the literature data, the presence of white matter hyperintensities is associated with lower CDT scores. 43 It may be that the low prevalence of severe WMLs in our study population prevented us from observing an association. Conversely, we confirmed that impaired CDT performance is associated with a higher Scheltens score, a hallmark of hippocampal atrophy 44 usually associated with poor episodic memory, especially in Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 83%
“…Grip strength is also reported to be associated with cognition (9). Moreover, although the association between white matter lesions (WMLs) on magnetic resonance images (MRI) and cognitive decline is well established (10), and these lesions are reported to be associated with lower CDT scores (11), it is not known whether CDT errors are associated with WMLs.…”
Section: Introductionmentioning
confidence: 99%